Chemical tradename dictionary - Ash, Michael (VCH Publishers, 1993)
This key reference will serve as the most comprehensive source for identifying and locating products in the international chemical marketplace. It has been written for the chemists, materials sientists, end-product formulators, industrial application specialists and scientists working in associated fields.